Facades-as-a-Service: Systemic managerial, financial, and governance innovation to enable a circular economy for buildings. Lessons learnt from a full-scale pilot project in the Netherlands - Azcárate-Aguerre, Juan F.; den Heijer, Alexandra C.; Arkesteijn, Monique H.; Vergara d’Alençon, Luz María; Klein, Tillmann (Frontiers in Built Environment, 2023)
Introduction: The challenge of the energy transition in the built environment has, in recent years, been exacerbated by rising awareness of the material resource limitations we face on the path towards sustainable development. In this context the concepts of Circular Economy (CE) and Product-Service Systems (PSS) have emerged as potentially complementary industrial and business strategies to overcome the interdependent material resource and clean energy challenges. Research significance: Research in the field of circular and PSS-based construction frequently centres on the design and engineering of products, mainly through technical strategies such as design for disassembly and adaptability, and the use of the different “R’s” (Reuse, Repair, Remanufacturing, etc.) to extend and/or reset the service lives of building materials and components. Such an approach often ignores the fact that these strategies require changes in the management, financing, and governance aspects of products and therefore buildings, throughout their entire service-lives. This paper will focus on the systemic administrative (i.e. management, financing, and governance) challenges of the circular and servitization transitions in the building and construction sector, to enable products which are “Circular by Design”, to effectively support regenerative processes. Research question: The paper asks how traditional building products’ management, financing, and governance processes prevent or delay the implementation of CE and PSS models. It explores the demand side’s perspective (commissioners, building owners and facility managers), taking a systemic view to the search for new practical, strategic, and scalable administrative models. Methodology: The research method applies the DAS model to data gathered from focus group discussion and co-design sessions involving multidisciplinary teams of experts from both academy and industry, as well as literature. The research was conducted within the context of the TU Delft Facades-as-a-Service full-scale pilot project. Results: The research has shown that, while PSS models to enable material circularity can be partially implemented within the current managerial, financial, and governance framework, this implementation is not efficient, effective, or scalable. This is because standard modes of operation in these disciplines are misaligned with that goal, resulting from this misalignment increase the complexity, risk perception, and therefore cost of PSS alternatives.